Growth and Inequality: Evidence from Transitional Economies - Oleksiy Ivaschenko (Center for Economic Studies and ifo Institute (CESifo), 2002)
The transitional economies of Eastern Europe (EE) and the former Soviet Union (FSU) experienced a dramatic increase in income inequality in the 1990s. In this paper I investigate the causes of unprecedented changes in income distribution using a unique panel of inequality estimates for 24 transitional countries for the period 1989-1998. The fixed effects model is used to control for unobservable country-specific effects that result in a missing-variable bias in cross-sectional studies. The relationship between income inequality, measured by Gini coefficient, and per capita GDP is shown to be positive for EE, but negative for the FSU. Economic liberalization, privatization and deindustrialization are found to have contributed to the rise in income inequality in the transitional region. Hyperinflation also makes the distribution of income more unequal. I do not find strong support for unemployment and the size of government consumption affecting income distribution. While civil conflicts increase income inequality, the extent of political rights and civil liberties is not found to directly affect income distribution.
Keywords: 330; economic growth; income distribution; transitional economies; panel data